Review article: Workplace violence in the emergency department: A systematic review and meta analysis. (12th April 2017) - Nikathil, Shradha; Olaussen, Alexander; Gocentas, Robert A; Symons, Evan; Mitra, Biswadev
Abstract: Patient or visitor perpetrated workplace violence (WPV) has been reported to be a common occurrence within the ED. No universal definition of violence or recording of such events exists. In addition ED staff are often reluctant to report violent incidents. The true incidence of WPV is therefore unclear. This systematic review aimed to quantify WPV in EDs. The association of WPV to drug and alcohol exposure was explored. The databases MEDLINE, Embase, PsycInfo and the Cochrane Library were searched from their commencement to 10 March 2016. MeSH terms and text words for ED, violence and aggression were combined. A meta‐analysis was conducted on the primary outcome variable‐proportion of violent patients among total ED presentations. A secondary meta‐analysis used studies reporting on proportion of drug and alcohol affected patients occurring within the violent population. The search yielded a total of 8720 records. A total of 7235 were unique and underwent abstract screening. A total of 22 studies were deemed relevant according to inclusion and exclusion criteria. Retrospective study design predominated, analysing mainly security records and incident reports. The rates of violence from individual studies ranged from 1 incident to 172 incidents per 10 000 presentations. The pooled incidence suggests there are 36 violent patients for every 10 000 presentations to the ED (95% confidence interval 0.0030–0.0043). WPV in the ED was commonly reported. There is wide heterogeneity across the study methodology, definitions and rates. More standardised recording and reporting may inform preventive measures and highlight effective management strategies.